2002
DOI: 10.1007/s005950200149
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Surgical Treatment of Pulmonary Hydatid Disease in Children: An Analysis of 35 Cases

Abstract: Parenchyma-saving surgical procedures such as cystotomy and capitonnage are the preferred methods of treatment for pulmonary hydatid disease in childhood. These simple procedures are safe, reliable, and successful. Combined medical treatment can be given but not as an alternative to surgery. Simultaneous surgical procedures for coexisting liver cysts may be preferred because of the lower morbidity rates and hospitalization. Ultrasound or computed tomography scanning should be done to detect coexisting liver cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
11
2
Order By: Relevance
“…Although the cysts occur more frequently in adult men this doesn’t demonstrate a sex tendency 1,6 . However, in children, there are various studies reporting higher frequencies in girls 9 or boys 2,3,10 . In our study, the male to female ratio was 1:1 in adults and the 3:1 in children.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Although the cysts occur more frequently in adult men this doesn’t demonstrate a sex tendency 1,6 . However, in children, there are various studies reporting higher frequencies in girls 9 or boys 2,3,10 . In our study, the male to female ratio was 1:1 in adults and the 3:1 in children.…”
Section: Discussioncontrasting
confidence: 58%
“…All patients were symptomatic in series that reported only on patients with huge cysts 13 and pleural complications 5 . Most common symptoms are cough, chest pain and sputum production 6,9,12,13 . Our findings regarding symptoms also support the literature.…”
Section: Discussionmentioning
confidence: 48%
“…19,23 Among these, capitonnage along with cystotomy has been the most frequently applied and recommended method. 22,24 Similarly, in our clinic, cystotomy and capitonnage in combination has been a common preference for hydatid cyst treatment. In cases with hepatic involvement accompanied by cysts located in the right lung, phrenotomy can be applied to remove the cyst in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…1,13,21,22 From the moment of definitive diagnosis based on certain symptoms, and the presence of ruptured or complicated cysts, surgical treatment should be planned as soon as possible. The aim of surgery is the complete resection of the cyst, suturing of the bronchiole openings, and the sterilization and closing of the cavity at the surgical site.…”
Section: Discussionmentioning
confidence: 99%
“…[3] A cyst is identifiable in chest x-ray and computed tomography (CT) scanning as a round or oval homogenous opacity that can be differentiated from pulmonary parenchyma. [4] Serological investigations have a limited value in diagnosis of lung hydatid cysts. [5] Some studies reported that in patients with pulmonary hydatid disease, the lung parenchyma should be preserved as much as possible and radical procedures must be avoided.…”
Section: Discussionmentioning
confidence: 99%